A rare human CEP290 variant disrupts the molecular integrity of the primary cilium and impairs Sonic Hedgehog machinery. Issue 1 (December 2018) - Kilander, Michaela; Wang, Chun-Hung; Chang, Chia-Hsiang; Nestor, Jonathan; Herold, Kevin; Tsai, Jin-Wu; Nestor, Michael; Lin, Yu-Chih
Abstract The primary cilium is a microtubule-enriched cell-communication organelle that participates in mechanisms controlling tissue development and maintenance, including cerebellar architecture. Centrosomal protein of 290 kDa (CEP290) is a protein important for centrosomal function and ciliogenesis. Mutations in CEP290 have been linked to a group of multi-organ disorders - termed ciliopathies. The neurophysiological deficits observed in ciliopathies are sometimes associated with the progression of autistic traits. Here, the cellular function of two rare variants of CEP290 identified from recent exome sequencing of autistic individuals are investigated. Cells expressing Cep290 carrying the missense mutation R1747Q in mouse exhibited a defective Sonic hedgehog (Shh) signalling response, mislocalisation of the Shh receptor Smoothened (Smo), and dysregulation of ciliary protein mobility, which ultimately disrupted the proliferation of cerebellar granule progenitors (CGPs). This data was furthermore corroborated in an autism patient-derived iPSC line harbouring the R1746Q rare CEP290 variant. Evidence from this study suggests that the R1746Q mutation interferes with the function of CEP290 to maintain the ciliary diffusion barrier and disrupts the integrity of the molecular composition in the primary cilium, which may contribute to alterations in neuroarchitecture.